2015
DOI: 10.14720/aas.2014.103.1.06
|View full text |Cite
|
Sign up to set email alerts
|

The characterisation of Vitis vinifera ’Refošk’ with AFLP and SSR molecular markers and ampelographic traits

Abstract: The genetic diversity and ampelographic variability of autochthonous red wine cultivar 'Refošk' (Vitis vinifera L.) grown in Slovenia were evaluated with AFLP molecular markers and OIV descriptors, respectively. SSR molecular markers were employed to confirm cultivar identity of analysed samples. Eight AFLP primer combinations, one was monomorphic, produced 16 polymorphic markers in 41 out of 113 samples, what classified samples into monomorphic and polymorphic group. Dendrogram constructed with simple matchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…In fact, the comparison of the ampelographic and ampelometric characteristics of traditional Moroccan grape varieties with other Mediterranean grape varieties has confirmed the existence of a significant diversity but also a resemblance of some ampelographic characteristics, in particular the shape of the berry and the color of the epidermis. For the character of the shape of the berry, we note a dominance of the spherical and short elliptical shape among Moroccan grape varieties; the same results were obtained in varieties from Montenegro [14], Palestine [15], Slovenia [16] and in Spain [17]. With regard to the color of the epidermis, it has been observed that almost all Moroccan grape varieties are yellow-green and blue-black in color, a finding which is in line with the results of the work carried out on grape varieties from Spain [18].…”
Section: Discussionsupporting
confidence: 73%
“…In fact, the comparison of the ampelographic and ampelometric characteristics of traditional Moroccan grape varieties with other Mediterranean grape varieties has confirmed the existence of a significant diversity but also a resemblance of some ampelographic characteristics, in particular the shape of the berry and the color of the epidermis. For the character of the shape of the berry, we note a dominance of the spherical and short elliptical shape among Moroccan grape varieties; the same results were obtained in varieties from Montenegro [14], Palestine [15], Slovenia [16] and in Spain [17]. With regard to the color of the epidermis, it has been observed that almost all Moroccan grape varieties are yellow-green and blue-black in color, a finding which is in line with the results of the work carried out on grape varieties from Spain [18].…”
Section: Discussionsupporting
confidence: 73%